Performance modelling and analysis of mobile grid computing systems. (1st January 2014) - Behera, Itishree; Tripathy, Chita Ranjan
Mobile grid computing has gained immense importance with academics, industry and the military. The performance issues such as load balancing, fault tolerance and reliability are quite important in mobile grid environments. In this paper, a decentralised load balancing model with fault tolerance for mobile grid computing system is proposed. Two algorithms are proposed: one for decentralised load balancing and the other for fault tolerance. The efficiency and time complexity of the proposed algorithms are found better compared to the existing works. The paper also proposes a method for modelling the reliability of mobile grid. Two terminal reliability of mobile grid computing system has been evaluated using the proposed model. The simulation results are presented.